2014
DOI: 10.5935/1984-6835.20140030
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Ecological Aspects of Male and Female Specimens ofCecropiaLoefl. (Urticaceae)

Abstract: Cecropia Loefl. (Urticaceae) species are popularly known in Brazil as embaúbas. This genus consists of dioecious, pioneer and medicinal trees. The leaves and inflorescences of Cecropia are part of the diet of various animals, mainly frugivorous mammals. Little is known about the chemical profile of the reproductive parts of embaúbas, the benefits of their consumption or even how the sex of the specimen influences this profile. Samples of female inflorescences of Cecropia glaziovii Snethl. and C. pachystachya T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…These species has an important role in natural regeneration process of vegetation in areas that were completely deforested. 3 The scientific interest on Cecropia has emerged from the traditional use of in folk medicine. 4 Within the genus Cecropia, for example the species C. glaziovii, C. Previous studies confirmed the presence of secondary metabolites in genus Cecropia such as benzoic acid, cinnamic acid, flavonoids (kind flavone, flavonol, flavan-3-ol or cathechin and flavolignan) tannins, and triterpenes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These species has an important role in natural regeneration process of vegetation in areas that were completely deforested. 3 The scientific interest on Cecropia has emerged from the traditional use of in folk medicine. 4 Within the genus Cecropia, for example the species C. glaziovii, C. Previous studies confirmed the presence of secondary metabolites in genus Cecropia such as benzoic acid, cinnamic acid, flavonoids (kind flavone, flavonol, flavan-3-ol or cathechin and flavolignan) tannins, and triterpenes.…”
Section: Introductionmentioning
confidence: 99%
“…4 Within the genus Cecropia, for example the species C. glaziovii, C. Previous studies confirmed the presence of secondary metabolites in genus Cecropia such as benzoic acid, cinnamic acid, flavonoids (kind flavone, flavonol, flavan-3-ol or cathechin and flavolignan) tannins, and triterpenes. 3 Considering the main studies about plants belonging to the genus Cecropia they are pointed out as follows.…”
Section: Introductionmentioning
confidence: 99%